Pelatihan Emotional Spiritual untuk Meningkatkan Kesadaran Diri Remaja di SMP N 2 Karanganyar - Novita Tri Jayanti; Woro Ayu Priyanggraeni; Lisnawati Ruhaena (Abdi Psikonomi, 2023)
The challenges faced by students today are enormous due to the influence of the environment and the rapid development of technology. Due to technological developments, especially social media and self-control and weak spiritual power, the level of self-awareness of students decreases as seen from the increase in negative behavior of adolescents. In overcoming this, the emotional-spiritual training with the project based learning method is designed to be able to increase students' self-awareness. The research subjects were 32 students of class VIII D at SMP Negeri 2 Karanganyar who were in the age range of 13-14 years. Methods The training is delivered using multimedia, starting with introductory games, lectures, discussions, and reflections through project posters. In the average (mean) pretest results, the results were 54,031 and 57,000 for the posttest average results. The results of data analysis showed a t-value of -5.094 with a significance of 0.000 (p <0.05). So it can be concluded that emotional-spiritual training can increase students' self-awareness.